Morphological Analysis of Major Segments of Coronary Artery Occlusion: Importance in Myocardial Revascularization Surgery - Martínez González, Brenda; Theriot Girón, María del Carmen; López Serna, Norberto; Morales Avalos, Rodolfo; Quiroga Garza, Alejandro; Reyes Hernández, Cynthia Guadalupe; Villanueva Olivo, Arnulfo; Leyva Villegas, Jorge I; Soto Domínguez, Adolfo; De la Fuente Villarreal, David; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (2015)
Revascularization surgery should ensure morphological similarity between the coronary artery and the graft. This is an important factor for its duration and permeability. The aim of this study was to analyze the morphological characteristics and morphometrics of the coronary artery segments with greater occlusion. This was an observational, cross-sectional descriptive study that consisted of two phases. A macroscopic phase in which 11 cadaveric hearts were extracted and coronary dominance and length of the anterior interventricular artery (AIA), the right coronary artery (RCA) and the circumflex artery (CXA) were determined. In the microscopic phase a total of 77 segments of these arteries were obtained and the luminal diameter, wall thickness, and amount of elastic fibers and the presence and size of the atheroma were determined. Right coronary dominance was the most frequent. Total vessel length was 15.65±1.17 cm for the AIA, 12.67±2.02 cm for the RCA and 8.79±2.5 cm for the CXA. Diameters ranged from 2.3 mm in the proximal segments and between 1.1 mm to 1.8 mm in the distal segments. Wall thickness in the proximal segments was between 354 µm and 396 µm and in the distal segments it ranged from 120 µm to 305 µm. The amount of elastic fibers showed that they were muscular arteries. Atheromas were present in 35% in the CXA, and in 32.5% in the AIA and the RCA. The largest ones were found in the proximal segments. This study examined the morphology and morphometry of the segments of the coronary arteries that are more frequently occluded. It provides information on the most significant parameters to be considered for election of the vascular graft in myocardial revascularization surgery.